The Effect Of Spiritual Well-Being On The Quality of Life Of Students In East Kalimantan - Aryadi, Aryadi; Hamka, Hamka; Haq, Aniq Hudiyah Bil (MOTIVA: JURNAL PSIKOLOGI, 2025)
Spiritual well-being is a crucial aspect for students in East Kalimantan, which can significantly impact their quality of life. This study examines the impact of spiritual well-being on the quality of life of students in East Kalimantan. This study uses quantitative research with simple random sampling techniques on students (n=475) in East Kalimantan. The data collection method for this study was conducted online using the spiritual well-being scale from Ellison and the WHOQOL-BREF Quality of Life scale, which were analyzed using linear regression analysis techniques, using SPSS software, version 23. Based on the hypothesis test, there is an influence of spiritual well-being on quality of life of r=0.344 with a significance of 0.00 (p<0.05), with a percentage of 34.4%, indicating that 65.6% is influenced by other factors. This shows that spirituality can be one of the factors in improving the quality of life of students. The implication of this study is that it can be utilized by academic counselors and educators to integrate value-based and spiritual approaches into student guidance and mentoring. Therefore, it is important for higher education institutions in East Kalimantan to develop programs that support student mental well-being.